THE SELECTION TOOLS FORMULATION IN A FORM OF BASIC COMPETENCE TEST AND FIELD SPECIFIC COMPETENCE TEST FOR CIVIL SERVANT CANDIDATE RECRUITMENT IN INDONESIA: A CASE STUDY AT INDONESIA INSTITUTE OF SCIENCES - Handoko, Tyas Wida; Jannah, Lina Miftahul (Universitas Muhammadiyah Mataram, 2020)
Abstrak: Masih ada 43% dari 4.450.000 Pegawai Negeri Sipil (PNS) di Indonesia yang memiliki kualifikasi pendidikan Sekolah Menengah Atas (SMA) menghambat kinerjaÂ Pemerintah Indonesia. Lebih lanjut lagi, 32,6 % dari total PNS di Indonesia mendekati usia pensiun. Keadaan itu mendorong Pemerintah Indonesia melaksanakan rekrutmen Calon Pegawai Negeri Sipil (CPNS). Studi ini membahas penyusunan perangkat seleksi di rekrutmen CPNS. Perangkat seleksi tersebut adalah Tes Kompetensi Dasar (TKD) dan Tes Kompetensi Bidang (TKB). Studi ini dilakukan melalui pendekatan post positivist dengan studi kasus di Lembaga Ilmu Pengetahuan Indonesia (LIPI). Wawancara mendalam dengan aktor sentral dalam penyusunan perangkat seleksi menjadi sumber pengumpulan data primer. Studi ini melihat perangkat seleksi melalui lima dimensi dari perangkat seleksi yang efektif yaitu reliabilitas, validitas, generalisasi, utilitas, dan legalitas. Penyusunan TKD dilakukan oleh Kementerian Pendidikan dan Kebudayaan sedangkan penyusunan TKB dilakukan oleh tim khusus di LIPI. Studi ini menunjukkan bahwa hampir semua aspek perangkat seleksi efektif sudah terimplementasi. Aspek yang belum terimplementasi adalah tahap testing dari perangkat seleksi tersebut. Beberapa tantangan penyusunan juga terungkap dalam studi ini. Manfaat dari studi ini adalah memberikan saran berbasis riset kepada Pemerintah Indonesia untuk mengembangkan perangkat seleksi yang lebih baik di masa yang akan datang.Â Abstract:Â The fact that from among 4.450.000 civil servants in Indonesia, as many as 42% are still senior high school graduates hampers the Indonesian government from achieving organizational goals effectively. In addition, as much as 32,6% of civil servants are elderly human resources approaching retirement age. Such conditions force Indonesian government to take an option of recruiting Civil Servant Candidate. This study discusses the preparation issue of the selection tool used to screen the applicants during the recruitment process. The selection tool in question are Basic Competence Test and Field Specific Competence Test. A post positivist case study was conducted at the Indonesian Institute of Sciences. In-dept interviews with central stakeholders were used as data collection method. The study looked from five dimensions of effective selection tool which are reliability, validity, generatability, utility, and legality. The formulation of Basic Competence Test was conducted by Ministry of Education and Cultures while the formulation of Field Specific Competence Test was conducted by special team in Indonesian Institute of Sciences. The study shows that from mentioned dimensions, while most aspects were implemented in the formulation, the step missing was a tryout of those selection tools. The study also shows that the formulation faced several specific challenges in each competence test. Benefit of this study is to give research-based advice for Indonesian government in next Civil Servants Candidate recruitment process.